2020
DOI: 10.1080/21505594.2020.1713649
|View full text |Cite
|
Sign up to set email alerts
|

Twitching motility of Stenotrophomonas maltophilia under iron limitation: In-silico, phenotypic and proteomic approaches

Abstract: This study investigates the twitching ability of 28 clinical and five environmental strains of S. maltophilia grown under iron-depleted condition through in-silico, phenotypic and proteomics approaches. Rapid Annotations using Subsystem Technology (RAST) analysis revealed the presence of 21 targets of type IV pilus shared across S. maltophilia strains K279a, R551-3, D457 and JV3. The macroscopic twitching assay showed that only clinical isolates produced a zone of twitching with a mean of 22.00 mm under normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The genes that escaped detection encode mainly single components of multidomain flagellar and pili proteins. For instance, discussing the P. aeruginosa results, pilM is a part of the type IV pili among a lot others, such as pilT and pilP , which were detected 83 . pilH is embedded in an operon along with pilG , pilI , and pilJ 84 .…”
Section: Resultsmentioning
confidence: 99%
“…The genes that escaped detection encode mainly single components of multidomain flagellar and pili proteins. For instance, discussing the P. aeruginosa results, pilM is a part of the type IV pili among a lot others, such as pilT and pilP , which were detected 83 . pilH is embedded in an operon along with pilG , pilI , and pilJ 84 .…”
Section: Resultsmentioning
confidence: 99%
“…S. maltophilia ATCC 13637 showed a complete inhibition of twitching motility with AZM, but this was not the same as FO, which only caused a 19% decrease in the interstitial zone surface area. Kalidasan and Neela investigated twitching motility in S. maltophilia and found that 67.85% (19/28) of the isolates had twitching motility (Kalidasan & Neela, 2020), while Cruz-Córdova et al stated that 43.33% (13/30) of the isolates only showed twitching motility (Cruz-Córdova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of type IV pili in S. maltophilia virulence has not been sufficiently studied. Kalidasan and Neela (2020) have proposed a theoretical model for S. maltophilia type IV pilus based on Rapid Annotations using Subsystem Technology (RAST) analysis that provided high quality genome annotations for bacterial genomes across the whole phylogenetic tree, and previous reports on P. aeruginosa .…”
Section: Fimbriae and Pilimentioning
confidence: 99%